The Significance of a Public Art Gallery as an Education Centre in Kuching, Sarawak - Wong, Neng Lee; Wan Jamarul Imran, Wan Abdullah Thani; Mohamad Faizuan, bin Mat (UNIMAS Publisher, 2018)
Building a Public Art Gallery is a dream of many individuals in Kuching, Sarawak. Kuching possesses colourful multicultural identities and has been producing different types of art that reflect the uniqueness of these identities. However, until now no public art gallery serves as a platform for Sarawakian artists, particularly in Kuching, to display their artworks and crafts and at the same time educate the community. This paper compiles the literature review on the importance of a public art gallery as an education centre for the society. The data was collected using the qualitative method, focusing on in-depth interviews to identify and analyse why a public art gallery is vital in Kuching, Sarawak, like a lot of other states in Malaysia. The informants were selected by purposive sampling and then analysed using Data Analysis Lamnek. This paper analyses the informants’ perceptions. It concludes with a suggestion of a temporary public art gallery in Kuching, Sarawak and some future studies.